2011
DOI: 10.17221/164/2010-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Specific rotation and carbohydrate profile of Croatian unifloral honeys

Abstract: Primorac Lj., Flanjak I., Kenjerić D., Bubalo D., Topolnjak Z. (2011): Specific rotation and carbohydrate profile of Croatian unifloral honeys. Czech J. Food Sci., 29: 515-519.Specific rotation and carbohydrate profile of Croatian black locust (robinia pseudoacacia L.), sage (Salvia officinalis L.) and chestnut (Castanea sativa Mill.) honeys were determined. Fructose, glucose, sucrose, maltose (with cellobiose and trehalose), melezitose (with erlose), raffinose, and xylose were evaluated and quantified by HPLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 11 publications
2
14
1
Order By: Relevance
“…monosaccharides, this honey fulfilled the requirement corresponding to honeydew blends ("not less than 45 g/100 g for honeydew honey and blends of honeydew honey with blossom honey"). Therefore, the 70% minimum percentage of chestnut pollen proposed by Seijo et al (1997), OJEU (2007) and Escuredo et al 2012 In respect of our chestnut honeys' maltose data, they were higher than those described by Primorac et al (2011) and Escuredo et al (2013) for European chestnut honeys. Our maltose averages were similar to those reported for Spanish heather (Bentabol-Manzanares et al, 2014), honeydew (Mateo and Bosch-Reig, 1998; Bentabol-…”
Section: Sugar Compositioncontrasting
confidence: 52%
See 1 more Smart Citation
“…monosaccharides, this honey fulfilled the requirement corresponding to honeydew blends ("not less than 45 g/100 g for honeydew honey and blends of honeydew honey with blossom honey"). Therefore, the 70% minimum percentage of chestnut pollen proposed by Seijo et al (1997), OJEU (2007) and Escuredo et al 2012 In respect of our chestnut honeys' maltose data, they were higher than those described by Primorac et al (2011) and Escuredo et al (2013) for European chestnut honeys. Our maltose averages were similar to those reported for Spanish heather (Bentabol-Manzanares et al, 2014), honeydew (Mateo and Bosch-Reig, 1998; Bentabol-…”
Section: Sugar Compositioncontrasting
confidence: 52%
“…This foodstuff generally crystallizes faster with a fructose/glucose ratio (F/G) lower than 1.11; and a glucose percentage, a glucose/water ratio (G/W), a (glucosemoisture)/fructose ratio ((G -W)/F) and a melezitose percentage higher than 35%, 2.16, 0.49 and 10%, respectively. On the contrary, honeys with F/G higher than 1.33, and glucose content, G/W and (G -W)/F lower than 28%, 1.70 and 0.30 respectively, generally remain liquid for longer periods (Serra-Bonvehí, 1989;Sancho et al, 1991;Lupano, 1997;Manikis and Thrasyvoulou, 2001;Cavia et al, 2002;Smanalieva and Senge, 2009 The vast majority of the researchers reported that both chestnut and honeydew were the honeys that remained liquid for longest (Mateo and Bosch-Reig, 1997;Smanalieva and Senge, 2009;Primorac et al, 2011). Moderate crystallization tendency rates were found for heather honeys, in comparison with other honey types (Smanalieva and Senge, 2009;Escuredo et al, 2014), agreeing with our data.…”
Section: Crystallization Indexesmentioning
confidence: 99%
“…When the G/W ratio is under 1.7, a slowly crystallizing honey is produced [48,49]. The F/G and G/W ratios are also useful for the classification of unifloral honeys [4,22,47,48], in the case of honeydew honeys that are reported to remain liquid for the longest [50,51]. With respect to minor sugars, some trisaccharides are also used as markers of honeydew in honeys, especially, melezitose [20,49,52,53], erlose, or raffinose [50,54].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a distinguishing combination of quality parameters was applied which, besides the pollen number and sensory analysis, includes the determination of the physico-chemical parameters (Přidal et al 2002;Bogdanov et al 2007;Primorac et al 2011;Uršulin-Trstenjak et al 2013) Micro and micro elements proportions in honey. The proportions of Ca, Na, K, Mg, Zn, Fe, Cu, Mn, Al, Ni, Pb, and Cd in the black locust honey in both seasons and all the five regions studied varied in wide ranges, both between the regions and inside the regions (Table 2).…”
Section: Resultsmentioning
confidence: 99%